Apakah Model Financial Distress Dapat Memprediksi Tanda-Tanda Peringatan Dini Kesulitan Keuangan? - Ramadahniel Islami; Poppy Nurmayanti; Azwir Nasir; Ria Nelly Sari (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Financial distress is a stage of decline in a company's financial condition that occurs before bankruptcy and liquidation occurs in a company. However, if a company is experiencing financial distress it is uncertain that it will end in bankruptcy. This depends on the ability of a company to prevent and overcome financial distress conditions that will lead to bankruptcy. Bankruptcy occurs when the company is unable to meet its maturing obligations either from the company's current operating activities or from the company's mandatory payments. The study aims to find out whether the financial distress model can predict early signs of financial distress by using the Zmijewski, Springate and Grover models for manufacturing companies listed on the Indonesian stock exchange for the 2008-2017 period. This research uses quantitative methods. The sample selection technique used purposive sampling and obtained 100 companies included with a period of 10 years so that 1000 samples were observed. The analysis technique used in this study is panel data regression analysis using the Excel software application. The results showed that financial distress in the Zmijewski model contained 149 companies experiencing distress, springate 410 and grover 100 companies experiencing distress and an accuracy rate of 85,10% for the Zmijewski model, 59% for the springate model and 90% for grover. Thus giving the conclusion that the three models can predict effectiv in determining the financial distress of a company so that it can provide early warning system.